The ω-3 polyunsaturated fatty acid, eicosapentaenoic acid, attenuates abdominal aortic aneurysm development via suppression of tissue remodeling. - Jack H Wang; Kosei Eguchi; Sahohime Matsumoto; Katsuhito Fujiu; Issei Komuro; Ryozo Nagai; Ichiro Manabe (PLoS ONE, 2014)
Abdominal aortic aneurysm (AAA) is a prevalent vascular disease that can progressively enlarge and rupture with a high rate of mortality. Inflammation and active remodeling of the aortic wall have been suggested to be critical in its pathogenesis. Meanwhile, ω-3 polyunsaturated fatty acids such as eicosapentaenoic acid (EPA) are known to reduce cardiovascular events, but its role in AAA management remains unclear. Here, we show that EPA can attenuate murine CaCl2-induced AAA formation. Aortas from BALB/c mice fed an EPA-diet appeared less inflamed, were significantly smaller in diameter compared to those from control-diet-fed mice, and had relative preservation of aortic elastic lamina. Interestingly, CT imaging also revealed markedly reduced calcification of the aortas after EPA treatment. Mechanistically, MMP2, MMP9, and TNFSF11 levels in the aortas were reduced after EPA treatment. Consistent with this finding, RAW264.7 macrophages treated with EPA showed attenuated Mmp9 levels after TNF-α simulation. These results demonstrate a novel role of EPA in attenuating AAA formation via the suppression of critical remodeling pathways in the pathogenesis of AAAs, and raise the possibility of using EPA for AAA prevention in the clinical setting.